2022
DOI: 10.1002/cssc.202200543
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Low‐Impedance and High‐Passivated Interphase for Nickel‐Rich Cathode by Low‐Cost Boron‐Containing Electrolyte Additive

Abstract: The nickel-rich cathode LiNi 0.8 Co 0.1 Mn 0.1 O 2 (NCM811) possesses the advantages of high reversible specific capacity and low cost, thus regarded as a promising cathode material for lithiumion batteries (LIBs). However, the capacity of the NCM811 decays rapidly at high voltage due to the extremely unstable electrode/electrolyte interphase. The discharge capability at low temperature is also impaired because of the increasing interfacial impedance. Herein, a low-cost film-forming electrolyte additive with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 46 publications
(88 reference statements)
0
4
0
Order By: Relevance
“…The cracks intensify parasitic reactions between the NCM811 and electrolyte, leading to continuous depletion of active substances and rapid capacity loss. 29 Additionally, the cycled Li/NCM811 battery lacking 2,5BTBA exhibits characteristic mossy dendrites on the lithium metal anode, evident in Fig. 1e and f .…”
Section: Resultsmentioning
confidence: 91%
“…The cracks intensify parasitic reactions between the NCM811 and electrolyte, leading to continuous depletion of active substances and rapid capacity loss. 29 Additionally, the cycled Li/NCM811 battery lacking 2,5BTBA exhibits characteristic mossy dendrites on the lithium metal anode, evident in Fig. 1e and f .…”
Section: Resultsmentioning
confidence: 91%
“…The presence of a N-containing compound in the PFPN electrolyte proves that it can form a CEI with organic matter containing nitrogen. In N 1s spectra, -PN-P moieties were detected at the peak of 399.0 eV; however, the signal peak of nitrogen compounds was undetectable in the blank electrolyte. The rich P–O species (135.1 eV) observed in the P 2p spectrum (Figure d) could be partly attributed to the decomposition or polymerization of PFPN as well, and PN- moieties were detected at the peak of 134.2 eV, proving that PFPN could inhibit the dissociation of salt. In F 1s spectra (Figure c), the intensities of LiF are (684.8 eV) reduced, probably owing to the slow decomposition of LiPF 6 salt on the NCM811 cathode surface.…”
Section: Resultsmentioning
confidence: 97%
“…9−13 Particularly, the positively charged NCM811 has strong electrochemical activity especially at high voltage and varied temperature, resulting in a very unstable electrode/ electrolyte interface and electrolyte decomposition. 14,15 In order to solve the aforementioned issues, electrolyte additives have been employed and demonstrated an effective strategy to improve battery performance. For instance, anhydrides are believed to be beneficial to the batteries that are cycled at high temperature, 16,17 whereas benzenecontaining species are good for low-temperature capacity retention.…”
Section: Introductionmentioning
confidence: 99%
“…Rechargeable lithium-ion batteries (LIBs) as a clean energy storage technology has been successfully employed in a variety of applications, including electric vehicles, cell phones, and portable electronics. Recently, further performance improvements have been achieved through the development of Ni-rich cathodes, such as LiNi 0.8 Co 0.1 Mn 0.1 O 2 (NCM811). This cathode material is considered to be the most likely choice for the next generation of LIBs due to its high specific discharge capacity and cost-effectiveness when compared to other materials. , It has been demonstrated that raising the content of nickel in NCM typically increases the specific discharge capacity yet suffers from obvious capacity attenuation and performance degradation during cycling mainly due to the phase transformation and side reactions under high voltage. Particularly, the positively charged NCM811 has strong electrochemical activity especially at high voltage and varied temperature, resulting in a very unstable electrode/electrolyte interface and electrolyte decomposition. , …”
Section: Introductionmentioning
confidence: 99%